Risk Factor of Otitis Externa Patients - Atjo, M Farizan; Maharani, Ratih Natasha; Sanna, Andi Tenri (Formosa Journal of Science and Technology, 2024)
Otitis externa is an inflammation of the ear canal that can extend to the outer ear or tympanic membrane, commonly caused by bacteria, fungi, and viruses. Warm, humid environments and risk factors such as age, gender, body weight, physical activity, and environmental conditions contribute to its development. Symptoms include ear pain, discharge, itching, and occasionally hearing loss. This Narrative Review analyzed 10 articles from 2020 to 2024 to identify characteristic risk factors of otitis externa. Findings reveal that the condition predominantly affects late adolescents and individuals aged 17-40 years. The review concludes that otitis externa can occur in any age group or gender, with certain occupations, like those involving art materials, showing higher incidence rates, and diffuse otitis externa primarily impacting productive age patients.